Mouse polyomavirus utilizes recycling endosomes for a traffic pathway independent of COPI vesicle transport - Mannová, Petra; Forstová, Jitka (Journal of virology, 2003)
Mouse polyomavirus enters host cells internalized, similar to simian virus 40 (SV40), in smooth monopinocytic vesicles, the movement of which is associated with transient actin disorganization. The major capsid protein (VP1) of the incoming polyomavirus accumulates on membranes around the cell nucleus. Here we show that unlike SV40, mouse polyomavirus infection is not substantially inhibited by brefeldin A, and colocalization of VP1 with beta-COP during early stages of polyomavirus infection in mouse fibroblasts was observed only rarely. Thus, these viruses obviously use different traffic routes from the plasma membrane toward the cell nucleus. At approximately 3 h postinfection, a part of VP1 colocalized with the endoplasmic reticulum marker BiP, and a subpopulation of virus was found in perinuclear areas associated with Rab11 GTPase and colocalized with transferrin, a marker of recycling endosomes. Earlier postinfection, a minor subpopulation of virions was found to be associated with Rab5, known to be connected with early endosomes, but the cell entry of virus was slower than that of transferrin or cholera toxin B-fragment. Neither Rab7, a marker of late endosomes, nor LAMP-2 lysosomal glycoprotein was found to colocalize with polyomavirus. In situ hybridization with polyomavirus genome-specific fluorescent probes clearly demonstrated that, regardless of the multiplicity of infection, only a few virions delivered their genomic DNA into the cell nucleus, while the majority of viral genomes (and VP1) moved back from the proximity of the nucleus to the cytosol, apparently for their degradation.
Keywords: molekulární chaperony; Cell Nucleus; chaperon endoplazmatického retikula BiP; Lysosomes; COP-Coated Vesicles; Polyomavirus; rab5 GTP-Binding Proteins; brefeldin A; Rab5 proteiny vázající GTP; obalový protein; Molecular Chaperones; Endosomes; Rab proteiny vázající GTP; buněčné jádro; Capsid Proteins; Heat-Shock Proteins; virové plášťové proteiny; virion; lyzozomy; COP-vezikuly; Carrier Proteins; rab GTP-Binding Proteins; biologický transport; Brefeldin A; Animals; Endoplasmic Reticulum Chaperone BiP; Virion; zvířata; myši; Mice; Coatomer Protein; endozomy; transportní proteiny; Biological Transport; proteiny teplotního šoku